Body mass index and perioperative complications after oesophagectomy for adenocarcinoma: a systematic database review. Issue 5 (2nd May 2013) - Melis, Marcovalerio; Weber, Jill; Shridhar, Ravi; Hoffe, Sarah; Almhanna, Khaldoun; Karl, Richard C; Meredith, Kenneth L
Abstract : Objective: Given the increasing rate of obesity, the effects of excessive body weight on surgical outcomes constitute a relevant quality of care concern. Our aim was to determine the relationship between preoperative body mass index (BMI) on perioperative complications after oesophagectomy for adenocarcinoma of the oesophagus. Design: Retrospective database review. Setting: Single institution high volume oncological tertiary care referral centre. Participants: From our comprehensive oesophageal cancer database consisting of 709 patients, we stratified patients according to BMI: 155 normal-weight (BMI 20–24), 198 overweight (BMI 25–29) and 187 obese (BMI ≥30) patients. Interventions: All patients underwent oesophagectomy for cancer. Primary and secondary outcome measures: Incidences of preoperative risk factors and perioperative complications in each group were analysed. Results: The patient cohort consisted of 474 men and 66 women with a mean age of 64.3 years (28–86). They were similar in terms of demographics and comorbidities, with the exception of a younger age (65.2 vs 65.4 vs 62.5 years, p=0.0094), and a higher incidence of diabetes (9.1% vs 13.2% vs 22.7%, p=0.001), hiatal hernia (16.8% vs 17.8% vs 28.8%, p=0.009) and Barrett oesophagus (24.7% vs 25.4% vs 36.2%, p=0.025) for obese patients. The type of surgery performed, overall blood loss, extent of lymphadenectomy, R0 resections and complications were not influenced by BMI on univariate and multivariate analysis. Conclusions: In our experience, patients with an elevated BMI and oesophageal adenocarcinoma do not experience an increase in morbidity and mortality after oesophagectomy as stated in previous reports, when performed at a high volume centre. Additionally, BMI did not affect the quality of oncological resection as determined by number of harvested lymph-nodes and rates of R0 resections. Trial Registration: MCC 15030, IRB 105286.